2023
DOI: 10.1186/s10194-023-01552-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of super-responders vs. non-responders to CGRP(-receptor) monoclonal antibodies: a real-world experience

Abstract: Background Clinical trials and real-world studies revealed a spectrum of response to CGRP(-receptor) monoclonal antibodies (mAbs) in migraine prophylaxis, ranging from no effect at all to total migraine freedom. In this study, we aimed to compare clinical characteristics between super-responders (SR) and non-responders (NR) to CGRP(-receptor) mAbs. Methods We performed a retrospective cohort study at the Headache Center, Charité – Universitätsmediz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 58 publications
1
35
0
1
Order By: Relevance
“…Older age, lower MMDs and fewer previous treatment failures were also associated with >50% responders at three months in a real-world study (19). Similar to previous studies, unilateral localization, pulsatile nature (18,22), less comorbid MOH (22), fewer prophylactics used previously, and fewer baseline MMDs (19) were related to responders in our study. Regarding the effect of aura on clinical efficacy, in logistic regression analysis, the presence of aura did not remain a predictor of responders, but it was associated with ≥50% responders at six and 12 months.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Older age, lower MMDs and fewer previous treatment failures were also associated with >50% responders at three months in a real-world study (19). Similar to previous studies, unilateral localization, pulsatile nature (18,22), less comorbid MOH (22), fewer prophylactics used previously, and fewer baseline MMDs (19) were related to responders in our study. Regarding the effect of aura on clinical efficacy, in logistic regression analysis, the presence of aura did not remain a predictor of responders, but it was associated with ≥50% responders at six and 12 months.…”
Section: Discussionsupporting
confidence: 89%
“…In a multicenter study consisting of 864 patients with high-frequency EM or CM who received three types of CGRP mAbs for six months, it was found that the presence of unilateral pain, unilateral cranial autonomic symptoms and allodynia were predictors of responders (18). In a study of 260 patients with migraine receiving CGRP mAbs, typical migraine characteristics such as unilateral localization, pulsating character, photophobia or nausea were associated with ≥75% responders at three months, while CM, MOH, and concomitant depression were related to nonresponders (22). Older age, lower MMDs and fewer previous treatment failures were also associated with >50% responders at three months in a real-world study (19).…”
Section: Discussionmentioning
confidence: 99%
“…Among participants with chronic migraine, a positive effect of cabergoline was less obvious, which may relate to inadequate study power or a true lack of treatment efficacy in these participants. Our study population comprised only 13 participants with chronic migraine, which is particularly noteworthy since this group commonly exhibits a lower treatment response 20 also to CGRP-targeting therapies 21 . Migraine trials are characterized by a substantial placebo effect 22 and the larger placebo response in participants with chronic migraine in our study may accordingly be explained by a combination of more severe symptoms and a higher expectation of pain relief 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Real-world data on the monoclonal antibody galcanezumab also demonstrate similar results, indicating that the responder group had fewer headache days compared to the non-responder group (24.0 ± 6.4 vs. 26.0 ± 6.2, p ≤ 0.012) (129). When focusing on the comparison between CM and EM, a recent study comparing super responders (SR) and non-responders (NR) found that the percentage of CM in the NR group was higher than in the SR group (92% vs. 52%, p = 0.001) (130). However, in another real-world study using erenumab, it was found that fewer headache days were a good predictor only in the CM group and not in the EM group (131).…”
Section: Anti-cgrp Medication and Medication Underusementioning
confidence: 99%